Pengaruh Profitabilitas, Struktur Modal, dan Likuiditas Terhadap Nilai Perusahaan - Diranti, Hafiza; Diyani, Lucia Ari (JURNAL ONLINE INSAN AKUNTAN, 2025)
This study aims to examine the influence of profitability, capital structure, and liquidity on the firm value of the consumer goods sector. The data for this research is sourced from the financial reports of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. The method of analysis employed in this study is multiple regression analysis processed using SPSS 26. The research sample consists of 24 companies with a total data sample of 120, excluding 1 outlier. The results of this study indicate that profitability has a positive effect on firm value, capital structure has a negative effect on firm value, and liquidity has a negative effect on firm value. Furthermore, profitability, capital structure, and liquidity have a positive effect on the firm value of the consumer goods sector.   Keywords : Profitability, Liquidity, Capital Structure, Firm Value